Antioxidant Cream Formulation Type W/O Ethyl Acetate Extract of Rambutan Fruit Peel (Nephelium lappaceum L .) Waste with the DPPH Method - Febriani, Amelia; Kusuma, Ika Maruya; Zahra, Nada (Sainstech Farma: Jurnal Ilmu Kefarmasian, 2023)
Rambutan fruit peel contains phenolic chemical compound including geraniin and corilagin, which is a class of flavonoids, also elagic acid from tannin, which act as antioxidants and free radical scavengers. This study aimed to formulate a type water-in-oil (W/O) cream containing an ethyl acetate extract of rambutan peel and tested its antioxidant activity. The extraction of rambutan peel was carried out by maceration with an ethyl acetate solvent. The cream was made with a concentration of 5% rambutan peel extract, type W/O, and then its antioxidant activity was tested by the DPPH method using a UV-Vis spectrophotometer. Test for antioxidant activity in 5% cream of ethyl acetate extract of rambutan fruit peel was carried out at concentrations of 200, 100, 50, 25, and 12.5 ppm. The results showed that the organoleptic cream of ethyl acetate extract of rambutan fruit peel at 5% has a yellow-brown color, has a weak smell of rambutan peel, has characteristics that were not easily washed off with water, thick, and has a pH value of 5 (meets pH criteria) with water-in-oil cream type (W/O). The results of the antioxidant activity test of the ethyl acetate extract cream of rambutan peels had an IC50 value of 124.92 g/mL (moderate antioxidant category).